Painting with All the Colors: The Value of Social Identity Theory for Understanding Social Entrepreneurship - Pan, Nettra D.; Gruber, Marc; Binder, Julia (Academy of Management Review, 2019)
Building on the emerging body of research on founder identity, Wry and York (2017) elaborate how an identity-based approach has the potential to extend our knowledge of opportunity identification in social entrepreneurship. In particular, the authors draw on role identity theory (Stryker & Burke, 2000) and research on personal identity (Hitlin, 2003) to study hybrid identities within single individuals. While role and personal identity are useful constructs for studying entrepreneurial behavior, we are concerned about the foregone opportunity to use social identity theory for advancing our knowledge of social entrepreneurs as enterprising individuals, social venture creation processes, and related outcomes. Indeed, in this commentary, we argue that social identity theory holds more potential – than either role or personal identity theory – for analyzing the rich “other-oriented” behavior that is at the heart of social entrepreneurship.